Is the Use of Transanastomotic Tube Beneficial in Pyloric Atresia? - Mesut Demir, Serkan Odabaşi, Şeyma Demirci, Meltem Kaba, Nihat Sever, Abdullah Yildiz, Çetin Ali Karadağ, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Congenital pyloric atresia (CPA) is a rare gastrointestinal system anomaly characterized by gastric outlet obstruction. This study evaluated patients operated for CPA in the past 15 years. The impact of use or non-use of transanastomotic feeding tubes (TATs) on the follow-up results was examined. Material and Method: Patients operated for CPA between 2005 and 2020 were evaluated. Further, cases in whom TATs were used and cases in whom TATs were not used were evaluated in two sub-groups. The impact of presence orabsence of TATs on postoperative follow-up results was examined. Results: In this study, a total of 12 patients consisting of 7 boys and 5 girls were evaluated. The mean birth week was 35.1 ± 2.4 (31-38) weeks and the mean birth weight was 2602.9 ± 599.6 (1680-3620) grams. The mean time of operation was postnatal 3.8 (1-10) days. Among the cases, 8 (66.7%) had type 1 atresia, and 4 (33.3%) had type 2 atresia. Heineke-Mikulicz pyloroplasty was performed on 9 (75%) cases, and gastroduodenostomy was performed on 3 (25%) cases. 4 (33.2%) patients had various additional anomalies. The patient with EB (8.3%) died due to sepsis in the early postoperative phase. In 8 cases (66.7%), intraoperative TAT placement was performed. In cases with TATs, the time to postoperative feeding and length of stay were statistically determined to be lower. Discussion: Pyloric atresia is a rare intestinal system obstruction. Comorbidity with congenital anomalies increases mortality. Intraoperative TAT insertion enables early enteral feeding.